Protein kinase C involvement in cell cycle modulation. (18th September 2014) - Poli, Alessandro; Mongiorgi, Sara; Cocco, Lucio; Follo, Matilde Y.
Abstract : Protein kinases C (PKCs) are a family of serine/threonine kinases which act as key regulators in cell cycle progression and differentiation. Studies of the involvement of PKCs in cell proliferation showed that their role is dependent on cell models, cell cycle phases, timing of activation and localization. Indeed, PKCs can positively and negatively act on it, regulating entry, progression and exit from the cell cycle. In particular, the targets of PKCs resulted to be some of the key proteins involved in the cell cycle including cyclins, cyclin-dependent kinases (Cdks), Cip/Kip inhibitors and lamins. Several findings described roles for PKCs in the regulation of G1 /S and G2 /M checkpoints. As a matter of fact, data from independent laboratories demonstrated PKC-related modulations of cyclins D, leading to effects on the G1 /S transition and differentiation of different cell lines. Moreover, interesting data were published on PKC-mediated phosphorylation of lamins. In addition, PKC isoenzymes can accumulate in the nuclei, attracted by different stimuli including diacylglycerol (DAG) fluctuations during cell cycle progression, and target lamins, leading to their disassembly at mitosis. In the present paper, we briefly review how PKCs could regulate cell proliferation and differentiation affecting different molecules related to cell cycle progression.